Building a Financial Education Approach : A Starting Point for Financial Sector Authorities - World Bank (World Bank, Washington, DC, 2021)
While the importance of financial capability has been studied empirically, questions remain about program effectiveness, whether and how effectively these skills can be taught to consumers, and if financial education programs lead to sustained behavioral changes that improve one’s financial wellness and inclusion. When studied analytically, the results of financial education have been mixed. The objective of this report is to help guide financial sector authorities to build a more effective approach to financial education. The report synthesizes available resources and complements existing knowledge about financial education. It also explores the appropriate role for financial sector authorities within financial education and outlines a practical approach for financial sector authorities who choose to develop financial education agendas or strategies. Lastly, the report provides an overview of the best tools and practices to improve the effectiveness of financial education initiatives.